Frontostriatal activity and connectivity increase during proactive inhibition across adolescence and early adulthood. Issue 9 (15th February 2014) - Vink, Matthijs; Zandbelt, Bram B.; Gladwin, Thomas; Hillegers, Manon; Hoogendam, Janna Marie; van den Wildenberg, Wery P.M.; Du Plessis, Stefan; Kahn, René S.
Abstract During adolescence, functional and structural changes in the brain facilitate the transition from childhood to adulthood. Because the cortex and the striatum mature at different rates, temporary imbalances in the frontostriatal network occur. Here, we investigate the development of the subcortical and cortical components of the frontostriatal network from early adolescence to early adulthood in 60 subjects in a cross‐sectional design, using functional MRI and a stop‐signal task measuring two forms of inhibitory control: reactive inhibition (outright stopping) and proactive inhibition (anticipation of stopping). During development, reactive inhibition improved: older subjects were faster in reactive inhibition. In the brain, this was paralleled by an increase in motor cortex suppression. The level of proactive inhibition increased, with older subjects slowing down responding more than younger subjects when anticipating a stop‐signal. Activation increased in the right striatum, right ventral and dorsal inferior frontal gyrus, and supplementary motor area. Moreover, functional connectivity during proactive inhibition increased between striatum and frontal regions with age. In conclusion, we demonstrate that developmental improvements in proactive inhibition are paralleled by increases in activation and functional connectivity of the frontostriatal network. These data serve as a stepping stone to investigate abnormal development of the frontostriatal network in disorders such as schizophrenia and attention‐deficit hyperactivity disorder. Hum Brain Mapp 35:4415–4427, 2014. © 2014 Wiley Periodicals, Inc.